2013
DOI: 10.3748/wjg.v19.i32.5357
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms and associated factors in Chinese patients with functional dyspepsia

Abstract: Female sex, anxiety, and sleep disorder, weight loss, consulting a physician and prokinetic use during 1-year follow-up were associated with outcome of FD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
5
1
3
Order By: Relevance
“…Concerning smoking and alcohol, the results of scientific studies are controversial, their link with the onset of dyspeptic symptoms is poorly understood, thus, in a large Chinese serie, including 1049 patients with FD according to the Rome III criteria, in univariate analysis, alcohol is a factor related to FD (p = 0.024) [11]. In our study, neither chronic smoking nor alcohol consumption was significantly related to dyspeptic symptoms.…”
Section: Discussioncontrasting
confidence: 66%
“…Concerning smoking and alcohol, the results of scientific studies are controversial, their link with the onset of dyspeptic symptoms is poorly understood, thus, in a large Chinese serie, including 1049 patients with FD according to the Rome III criteria, in univariate analysis, alcohol is a factor related to FD (p = 0.024) [11]. In our study, neither chronic smoking nor alcohol consumption was significantly related to dyspeptic symptoms.…”
Section: Discussioncontrasting
confidence: 66%
“…Tabla 1. Características de los estudiantes de medicina según el consumo de alimentos en sitios de ventas ambulantes Las mujeres tuvieron una asociación positiva al padecimiento de dispepsia funcional, y esto fue reportado por investigaciones locales (4,14,15) e internacionales, en las que identificaron la asociación entre la sintomatología dispéptica y el sexo (valor p = 0,001) (16,17) .…”
Section: Resultsunclassified
“…For example, Zhen et al described bowel disturbances being significantly higher in rotating shift nurses compared to regular day nurses and that bowel symptom scores correlated with sleep disturbances positively 24 . Previous research has also shown that disruption of Stage 4 or slow-wave (deep) sleep, or the loss of rapid eye movement (REM) sleep, results in hyperalgesia or emergence of abdominal symptoms, such as nausea or cramping in healthy volunteers 15,[25][26][27] , and in patients with functional dyspepsia 12 or gastroesophageal reflux disease 28 . In addition, poor sleep quality (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested disrupted sleep quality in patients with dyspepsia compared to healthy controls, with published odds ratios ranging from 1.7 to 3.4 10 14 . However, some studies have not found this association 15 and others have found sleep apnea to be associated with irritable bowel syndrome rather than dyspepsia 16 18 . In addition, most research in this area has involved cross-sectional or case–control designs, providing limited information on the direction of causality.…”
Section: Introductionmentioning
confidence: 98%